PERKEMBANGAN SOSIAL ANAK USIA DINI ( USIA 5 – 6 TAHUN ) DI TK ISLAM PAS ASSAKIINAH MANTINGAN KAB NGAWI: SOCIAL DEVELOPMENT OF EARLY CHILDREN (AGE 5 – 6 YEARS) AT PAS ASSAKIINAH ISLAMIC KINDERGARTEN - Yudhiarti, Ndaru (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2023)
The ability to behave socially in early childhood needs to be educated from an early age. Obstructed social development can cause difficulties for children in developing themselves in the future. Humans are born as social beings, therefore positive social behavior is an important factor that needs to be educated from childhood. Because at an early age is a period of forming the foundation for one's social behavior. The inability of children to behave socially as expected by their environment can result in children being isolated from the environment, not forming self-confidence, withdrawing from the environment, and so on. ), school principals, and teachers of the PAS Assakiinah Islamic Kindergarten. The research data were obtained through interviews, observation, and documentation. The results of the study show that the social development of early childhood (age 5-6 years) in Assakiinah Islamic Kindergarten is different. However, the teacher seeks to carry out the formation of akhlakul karimah so that children have good social development. These efforts include planting social values ​​in schools and implementing learning strategies in the social development of early childhood.